2020
DOI: 10.1186/s13741-020-00162-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving agreement of ASA physical status class between pre-anesthesia screening and day of surgery by adding institutional-specific and ASA-approved examples: a quality improvement project

Abstract: Background A successful anesthesia pre-assessment clinic needs to identify patients who need further testing, evaluation, and optimization prior to the day of surgery to avoid delays and cancelations. Although the ASA Physical Status Classification system (ASA PS) has been used widely for over 50 years, it has poor interrater agreement when only using the definitions. In 2014, ASA-approved examples for each ASA physical status class (ASA PS). In this quality improvement study, we developed and evaluated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The ASA score is determined by pre-anesthetic medical co-morbidities. An ASA score of II or below indicates a patient with mild systemic disease ( 53 ). One study indicated a criterion of ASA risk score of III or less with a stable medical condition ( 52 ), while the other indicated an ASA score of I/II ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ASA score is determined by pre-anesthetic medical co-morbidities. An ASA score of II or below indicates a patient with mild systemic disease ( 53 ). One study indicated a criterion of ASA risk score of III or less with a stable medical condition ( 52 ), while the other indicated an ASA score of I/II ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…[26] Another real-world study by Abouleish et al of concordance between anesthesiologists in the preoperative clinic and on the day of surgery had similar results ( value 0.62), but subsequently demonstrated 'almost perfect' agreement ( value 0.85) after the introduction of examples that were ASA and institutionally approved. [27] The majority of the discordant scores were scored lower by surgeons, with the largest group comprising those assigned ASA 2 by the anesthesiologist but ASA 1 by the surgeon. We observed that patients with discordant ASA scores had a signi cantly higher proportion of comorbid clinical conditions (raised creatinine, diabetes mellitus on insulin, history of congestive heart failure, cerebrovascular accident, ischemic heart disease and smoking).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have shown that the addition of examples to the ASA score and reinforcement of its use were required to improve reliability. [27,29] Standardization efforts are needed to improve the utility of ASA scores in clinical practice and for uses beyond the original intention of communicating patient healthcare status.…”
Section: Discussionmentioning
confidence: 99%
“…Based on medical records, several factors were analyzed retrospectively. After identifying the patients' underlying health conditions from the medical history and clinical diagnosis, the patients' statuses, at the time of IR treatment, were classified retrospectively using the American Society of Anesthesiologists (ASA) physical status classification [4]. The primary cause of each cardiac arrest event was also speculated according to details documented in the respective operative reports.…”
Section: Methodsmentioning
confidence: 99%